The Analysis of Migration Processes in Russia According to the Census - Vorobieva, Olga Dmitrievna; Topilin, Anatoly Vasilyevich; Grebenyuk, Aleksandr Aleksandrovich; Lebedeva, Tamara Vasilyevna (Economy of Regions, 2016)
The subject matter of the study is the internal migration of the Russian population from I960 to 2010. The study is based on the information about the spatial population movements, published in the proceedings of the all-Union censuses of 1970, 1979, 1989, and of the all-Russian censuses of 2002 and 2010. The main flows and directions of migration are considered. The methodological analysis of the migration was performed by means of cross-cutting indicators to assess the dynamics of migration processes over a long period. Special attention is given to the rural-urban internal migration, as its volumes, patterns and impacts have not been adequately tested and evaluated to date. Relative indicators, which have not been used previously to assess the studied processes are proposed and calculated. To ensure the comparability of the materials of the censuses of the Soviet and post-Soviet periods under consideration, the economic zoning adopted prior to 2000 was used, and the uniformity of administrative scale was ensured. The hypothesis that from decade to decade, there was a decrease of the intensity of territorial mobility for both urban and rural populations is confirmed. The inter-regional migration flows are considered; the different trends and intensity of migration processes for more than four decades are specified. The dynamics of the structure of migrants on the basis of length of residence in the place of permanent residence in different regions is analyzed. The study has shown that the development and preservation of the prevailing trends in that period continues to adversely affect the territorial distribution of the population and the regional socio-economic development of the country. The findings can find their application in the correction of regional socio-economic and migration policies.